Student Online Business Readiness in the Perspective of Digital Mindset: Phenomenological Study on Students in Malang - Amelia Setyawati; Adelia Rahma; Brillian Rosy; Amelia Sugangga; Sudarjo Sudarjo; Hario Hario; Dieva Zahrohtu Anfi (International Forum of Researchers and Lecturers, 2025)
The development of digital technology has changed global business patterns, including in Indonesia, through the growth of e-commerce, social media, and online platforms. This change opens up great opportunities for students as the educated young generation to develop online businesses. This research aims to explore students' online business readiness from a digital mindset perspective through a phenomenological study approach among students in Malang. The research focuses on online business readiness, digital mindset, attitudes towards technology, and the contribution of entrepreneurship learning, which are analyzed using the Theory of Planned Behavior framework(Ajzen, 1991) and Entrepreneurial Mindset Theory. The research used qualitative methods with in-depth interviews with online business students. The results show that students have a basic understanding of digital business, especially in utilizing social media and marketplaces. A positive attitude towards technology has been formed, indicated by perceived benefits and ease of use. However, a gap emerges between technical skills and long-term strategic planning capabilities. Innovation and problem-solving tend to be reactive, simply following trends, while psychological resistance such as fear of fraud and data security remain barriers. This research confirms that online business readiness is not only determined by technical skills, but also by the strengthening of an adaptive, innovative digital mindset. This research confirms that online business readiness is not only determined by technical skills, but also by strengthening an adaptive, innovative, and resilient digital mindset.The novelty of this research is the integration of TPB and Entrepreneurial Mindset Theory to understand students' readiness to face digital business challenges.